2007
DOI: 10.1016/j.jhsb.2006.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Unilateral Upper Limb Muscular Hypertrophy Associated With Contracture of an Extrinsic Extensor Tendon

Abstract: We report a case of congenital unilateral upper limb muscular hypertrophy which presented with loss of extensor tendon excursion of a single digit in late adolescence. The reason for the problem arising is not clear and is not clearly explained by the underlying congenital pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Persistence of these aberrant muscles in this disease might account for the deformities seen in CMH, and therefore there is often non-uniformity of the affected limb. Hand deformities are also thought to be caused by imbalance of the extrinsic and intrinsic muscles (Imai et al, 2007;Takka et al, 2005). Dahan et al (2018) showed that the thumb tends to deviate to the radial and palmar side while the fingers tend to deviate ulnar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistence of these aberrant muscles in this disease might account for the deformities seen in CMH, and therefore there is often non-uniformity of the affected limb. Hand deformities are also thought to be caused by imbalance of the extrinsic and intrinsic muscles (Imai et al, 2007;Takka et al, 2005). Dahan et al (2018) showed that the thumb tends to deviate to the radial and palmar side while the fingers tend to deviate ulnar.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital muscular hypertrophy (CMH) was first reported by Lipscomb in 1960 and then by Mizuoka in 1962 (Mizuoka et al., 1962). Many terminologies have been used to describe this condition, including congenital unilateral hyperplasia of the hand (Takka et al., 2005), unilateral hypertrophy of the upper extremity (Imai et al., 2007), muscle hemihypertrophy, aberrant muscle syndrome or accessory muscle syndrome (Ogino et al., 2010). As a condition, CMH is characterized with overgrowth of one or two limbs caused by somatic gain-of-function mutation with mosaicism.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital muscular hypertrophy of the upper limb is an uncommon anomaly related to an idiopathic proliferation of skeletal muscles (Imai et al., 2007). Few cases have been described in the literature.…”
Section: Introductionmentioning
confidence: 99%